ANALISIS KINERJA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PALU DALAM PENERAPAN KARTU TANDA PENDUDUK ELEKTRONIK DI KOTA PALU - Pratama, Kristi Aria (Katalogis, 2013)
To analyze the performance of the Department of Population and Civil Registration Palu in implementation of e-ID cards in South Palu district. The problem in this study is how the performance of the Department of Population and Civil Registration of Palu in the implementation of e-ID cards in South Palu district?. This study uses the concept of performance theory Dwiyanto (1995:50) that where there are 5 performance concept that is composed of Productivity, Quality of Service, Responsiveness, Responsibility and Accountability. The research method used is a qualitative method. The technique of taking informants using purposive sampling method. From the research, Performance of Population and Civil Registration Palu in implementing e-ID application in the District of South Palu categorized performing well enough. Judging from the fifth dimension of service quality and performance aspects of Corporate Responsibility aspects included in the unfavorable category. Should be the work of the application associated with the element of stability or stability and can also be circumvented for all elements that are members in the organization. So that the existence and survival of the organization can be preserved and maintained, for the sake of continuity in achieving the vision and mission of the organization.